Synthesis of oxime bearing cyclophosphazenes and their reactions with alkyl and acyl halides - Çil, E; Arslan, M; Görgülü, AO (John Wiley & Sons Inc, 2006)
Two novel cyclophosphazenes containing oxime groups were prepared from the hexakis(4-formylphenoxy)cyclotriphosphazene (2) and hexakis(4-acetylphenoxy)cyclotriphosphazene (7). The reactions of these oximes with acetyl chloride, chloroacetyl chloride, methyl iodide, propyl chloride, monochloroacetone, and 1,4-dichlorobutane were studied. Hexasubstituted compounds were obtained from the reactions of hexakis(4-[(hydroxyimino)methyl]phenoxy)cyclotriphosphazene (3) with acetyl chloride (4) and chloroacetyl chloride (5); however, tetra-substituted product was obtained from methyl iodide (6). Tetra- and trisubstituted products were obtained from the reactions of hexakis(4-[(1)-N-hydroxyethaneimidoyl]phenoxy)cyclotriphosphazene (8) with acetyl chloride (9) and chloroacetyl chloride (10), respectively. All products were obtained in high yields. Pure and defined product could not be obtained from the reaction of 8 with methyl iodide, and could not be also obtained from the reactions of 3 and 8 with propyl chloride, monochloroacetone, and 1,4-dichlorobuthane. The structures of the compounds were defined by elemental analysis, IR, H-1, C-13, and P-31 NMR spectroscopy. (c) 2006 Wiley Periodicals, Inc.
Keywords: Dichlorophosphoryl-P-Trichlorophosphazene; Linear Phosphazenes; Nitrile Spacer; Yeast-Cells; Derivatives; Bacterial; Cyclotriphosphazenes; Pt(Ii); Iron